Determinants of Financial Performance in Primary Consumer Goods Companies on the Indonesia Stock - paniran; Siti Mudawanah (Journal of Economy, Accounting and Management Science (JEAMS), 2026)
Financial performance reflects a company's financial condition through an analysis of financial statements that allow for an assessment of the good or bad condition as a reflection of the company's performance. This study aims to analyze the influence of the Board of Directors, Board of Commissioners, Audit Committee, Debt to Asset Ratio (DAR), and company size on Return on Assets (ROA) as an indicator of financial performance in primary consumer goods sector companies listed on the Indonesia Stock Exchange (IDX) during the period 2019 to 2023. The research method used is quantitative by utilizing secondary data. The population in this study includes 124 companies from the sector, and 46 companies were selected as samples through a purposive sampling technique. Data analysis was carried out using multiple linear regression with the help of SPSS version 25 software. The results of the study indicate that partially, each variable, namely the Board of Directors, Board of Commissioners, Audit Committee, DAR, and company size has a significant influence on ROA. Simultaneously, the five variables also show a significant influence on ROA as the dependent variable.